The species distribution model based on the random forest algorithm reveals the distribution patterns of Neophocaena asiaeorientalis - Rongcheng, Rao; Yi, Huang; Jialing, Min; Ying, Yang; Fanning, Liu; Xiya, Wu; Xinyuan, Shi; Caigang, Li; Yingen, Dai; Qinghai, Huang; Jinxiang, Yu; Jianglong, Que (Scientific reports, 2025)
The Species Distribution Model (SDM) provides a crucial foundation for the conservation of the Yangtze finless porpoise (YFP), a critically endangered freshwater cetacean endemic to China. In this study, we conducted population and habitat surveys, and employed the Random Forest algorithm (RF) to construct SDMs. We found that the habitat preference of YFP shows complex seasonality. Cyanobacteria and total phosphates have been identified as the predominant factors influencing the YFP distributions by affecting prey resources. We emphasize that ascertaining the presence and pseudo-absence points of YFP, in conjunction with the selection of key factors, constitutes the foundational element in the construction of SDMs. We suggest that the incorporation of techniques such as environmental DNA could expand the range of environmental factors, particularly with regard to the distribution of prey resources at the genus or species level. This study provides guidance for the SDMs of YFP and demonstrates the potential of machine learning algorithms in constructing SDMs for the endangered aquatic species.